2014
DOI: 10.3233/fi-2014-1046
|View full text |Cite
|
Sign up to set email alerts
|

Application of Rough Set Theory to Prediction of Antimicrobial Activity of Bis-Quaternary Imidazolium Chlorides

Abstract: The paper investigates relationships between chemical structure, surface active properties and antibacterial activity of 70 bis-quaternary imidazolium chlorides. Chemical structure and properties of imidazolium chlorides were described by 7 condition attributes and antimicrobial properties were mapped by a decision attribute. Dominance-based Rough Set Approach (DRSA) was applied to discover a priori unknown rules exhibiting monotonicity relationships in the data, which hold in some parts of the evaluation spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Previous research in this area [ 8 , 16 , 17 ] has shown that good antimicrobial activity for a group of analyzed gemini chlorides is related to n-spacer equal to or longer than 6 atoms of carbon. Moreover, we discovered more features in a strong relationship with a good antifungal activity, regarding Candida albicans strains.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research in this area [ 8 , 16 , 17 ] has shown that good antimicrobial activity for a group of analyzed gemini chlorides is related to n-spacer equal to or longer than 6 atoms of carbon. Moreover, we discovered more features in a strong relationship with a good antifungal activity, regarding Candida albicans strains.…”
Section: Resultsmentioning
confidence: 99%